ANALISIS KELAYAKAN DAN PROFITABILITAS USAHA KERIPIK PISANG PADA KWT SATYA GEMILANG DI DESA SINDANGSARI KECAMATAN SAJIRA KABUPATEN LEBAK - Akhmad Hidayatullah (Jurnal Humaniora & Sosial Sains, 2026)
Business feasibility analysis is an activity that studies in depth about a business or business being run, in order to determine whether or not the business is feasible to run. The Satya Gemilang Women Farmers Group in Sindangsari Village manages a household-scale banana chips business with a simple production process. This business is a source of additional income for the women of the Satya Gemilang Women Farmers Group (KWT). This study aims to analyze the feasibility and profitability of the banana chips business managed by the Satya Gemilang Women Farmers Group (KWT) in Sindangsari Village, Sajira District, Lebak Regency. This study was conducted in January 2026 with the research methods used being descriptive and quantitative analysis. Data analysis was carried out using the R/C ratio and profitability techniques. The results of the study indicate that the KWT Satya Gemilang banana chips business has promising prospects and provides financial benefits with a net income of Rp 734,500/per month. Based on the analysis results, the R/C ratio value of 1.25 indicates that it meets the financial feasibility requirements, which means the income generated is sufficient to cover production costs and generate profits. The profitability level of the KWT Satya Gemilang banana chips business is 20.55%.